The effects of oral discussion and text chat on L2 Chinese writing. (4th November 2020) - Kessler, Matt; Polio, Charlene; Xu, Cuiqin; Hao, Xuefei
Abstract: Numerous studies have investigated the effects of prewriting tasks on writing quality and language (e.g., individual vs. collaborative planning, text‐chat vs. face‐to‐face [FTF] discussion, etc.). Recent meta‐analyses have found a small advantage for text chat on writing, but no studies involved logographic languages, for which character learning may limit and tax language production. In this study we explore this issue, as university learners of Chinese ( N  = 10) engaged in prewriting discussions orally and via text chat followed by a timed‐writing task. Results show that during FTF planning, students engaged in talk that was greater in terms of discussion length and number of turns; in students' writing, FTF planning resulted in increased lexical complexity and syntactic richness. Our results contradict theoretical perspectives suggesting that text chat might be more advantageous, as well as one empirical study by Liao. Finally, we discuss the implications for learning to write in a non‐alphabetic language. The Challenge: Researchers have explored the effects of pre‐task planning modes (e.g., face‐to‐face versus text chat) on learners' writing performance, finding advantages for text chats.  However, English has traditionally been the L2 investigated rather than logographic languages (e.g., Chinese).  Do such findings hold true with non‐alphabetic languages?  Which pre‐task planning mode is more beneficial?